Regiões funcionais brasileiras: dinâmica recente, policentricidade e relocalização seletiva da atividade econômica - Cassiano Ricardo Dalberto (2018)
Over the last decades, works that seek to investigate and understand the relationships between urban centers and their surroundings have been gaining importance in regional economic literature. In this sense, the city-region concept deserves to be highlighted, since it provides a theoretical substrate capable of encompassing the socio-economic structures and dynamics possible in such scope. Among the factors that characterize the city-regions is the integration of the local labor market, whose empirical representation in space can be given by the functional regions. These include geographical delimitations that traditionally take account of commuting movements, aiming to define the spatial dimension of the labor market - something that has already been officially carried out by several countries, especially in Europe and the United States. The present thesis, then, has a double objective: to define functional regions for Brazil and, using such delimitations, to investigate the recent evolution of the spatial division of labor and the centrality of the urban networks of these regions. For the construction of the functional regions, we used commuting flows obtained from the Censuses of 1980, 2000 and 2010, applying methods of network analysis. The study then develops over the 26 main functional regions, constituted by the Brazilian largest urban centers. Among the results obtained, we observe that the productive deconcentration in the recent decades is spatially more circumscribed than previously suggested in the literature, occurring mainly within the surroundings of the main national urban nuclei. In addition, although there is also a deconcentration of activities that are at the forefront of the recent productive changes, such movement is less intense than the one observed in general for the other activities. Also, the urban center of São Paulo has increased its concentration in such activities over the last years. At the same time, employment in the surroundings of the functional regions became more sectorially diversified, indicating a greater economic autonomy of these places and increasing their productive complementarities with the nuclei. Finally, it should be pointed out that even with the monocentric structure of the regional urban networks tending to decrease over time, this movement has occurred in concentrating terms, with the secondary centers gaining polarizing force more to the detriment of other municipalities of smaller size than to the nucleus of the functional region.